Soft and Hard Tissue Management in Implant Therapy—Part II: Prosthetic Concepts - Paolo Francesco Manicone; Luca Raffaelli; Marjan Ghassemian; Antonio D'Addona (International Journal of Biomaterials)
The ongoing pursuit of aesthetic excellence in the field of implant therapy has incorporated prosthetic concepts in the early treatment-planning phase, as well as the previously discussed surgical concepts. The literature has addressed these prosthetic and laboratory approaches required to enhance and perfect the soft and hard tissue management (SHTM). After surgically providing an acceptable hard tissue architecture and adequate timing of loading of the implant, the prosthetic phase is responsible for the soft tissue modeling, through correctly planned and executed procedures, which induce a satisfactory soft tissue profile by considering the microvasculature, the abutment connection and positioning, and the implementation of an adequate provisional phase. The objectives are the modeling of the soft tissues through the use of a conforming periorestorative interface which will produce desired and stable results.